Examining co-based nanocrystals on graphene using low-voltage aberration-corrected transmission electron microscopy. - Warner, J; Rümmeli, M; Bachmatiuk, A; Wilson, M; Büchner, B (2010)
We present a method to produce graphene and few layer graphene sheets using solution phase chemistry, which are used as ultrathin support membranes for enhanced imaging of nanomaterials using transmission electron microscopy. We demonstrate this by decorating the surface of the graphene sheets with Co-based nanocrystals (CoCl(2) and hcp Co). Low-voltage aberration-corrected high resolution transmission electron microscopy at 80 kV is used to image the nanocrystals on the thin graphene supports. We show that electron beam irradiation causes the CoCl(2) nanocrystals to become mobile on the graphene surface and exhibit both rotational and translational motion. We provide real-time in situ monitoring with atomic resolution of the coalescence of two CoCl(2) nanocrystals on the graphene surface, driven by electron beam irradiation. The CoCl(2) nanocrystals are then annealed in vacuum and transform into Co nanocrystals with hcp crystal structure. We show that these Co nanocrystals are catalytic and electron beam irradiation leads to the etching of the graphene surface, not observed for the CoCl(2) nanocrystals.